Dysbiosis index and fecal concentrations of sterols, long-chain fatty acids and unconjugated bile acids in dogs with inflammatory protein-losing enteropathy - Cagnasso, Federica; Suchodolski, Jan S.; Borrelli, Antonio; Borella, Franca; Bottero, Enrico; Benvenuti, Elena; Ferriani, Riccardo; Tolbert, M. Katherine; Chen, Chih-Chun; Giaretta, Paula R.; Gianella, Paola (Frontiers in Microbiology, 2024)
Introduction: Canine protein-losing enteropathy (PLE) is a syndrome characterized by gastrointestinal loss of proteins. While fecal microbiome and metabolome perturbations have been reported in dogs with chronic enteropathy, they have not been widely studied in dogs with PLE. Therefore, the study aims were to investigate gut microbiome and targeted fecal metabolites in dogs with inflammatory PLE (iPLE) and evaluate whether treatment affects these changes at short-term follow-up. Methods: Thirty-eight dogs with PLE and histopathological evidence of gastrointestinal inflammation and 47 healthy dogs were enrolled. Fecal samples were collected before endoscopy (T0) and after one month of therapy (T1). Microbiome and metabolome alterations were investigated using qPCR assays (dysbiosis index, DI) and gas chromatography/mass spectrometry (long-chain fatty acids, sterols, unconjugated bile acids), respectively. Results: Median (min-max) DI of iPLE dogs was 0.4 (-5.9 to 7.7) and was significantly higher (p < 0.0001) than median DI in healthy dogs (-2.0 (-6.0 to 5.3)). No significant associations were found between DI and selected clinicopathological variables. DI did not significantly differ between T0 and T1. In iPLE dogs, at T0, myristic, palmitic, linoleic, oleic, cis-vaccenic, stearic, arachidonic, gondoic, docosanoic, erucic, and nervonic acids were significantly higher (p < 0.0001) than healthy dogs. In iPLE dogs, oleic acid (p = 0.044), stearic acid (p = 0.013), erucic acid (p = 0.018) and nervonic acid (p = 0.002) were significantly decreased at T1. At T0, cholesterol and lathosterol (p < 0.0001) were significantly higher in iPLE dogs compared to healthy dogs, while total measured phytosterols were significantly lower (p = 0.001). No significant differences in total sterols, total phytosterols and total zoosterols content were found at T1, compared to T0. At T0, total primary bile acids and total secondary bile acids did not significantly differ between healthy control dogs and iPLE dogs. No significant differences in fecal bile acid content were found at T1. Discussion: Dysbiosis and lipid metabolism perturbations were observed in dogs with iPLE. Different therapeutic protocols lead to an improvement of some but not all metabolome perturbations at shortterm follow-up.